Postcards from Beazley and other electric dreams : notes from the 15th International Congress of Classical Archaeology - Rajala, Ulla
Classical archaeologists gathered in Amsterdam at their quinquennial congress this summer. Some of the key papers contributed to the on-going theoretical and methodological debate between traditionalists and relativists, while other speakers presented new computer techniques and interesting findings.